2008
DOI: 10.1111/j.1532-5415.2008.02069.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Geriatrician‐Led Hip Fracture Program: Improvements in Clinical and Economic Outcomes

Abstract: The hip fracture service (HFS) is an interdisciplinary, geriatrician-led program instituted to improve the care of frail elderly people who present to the hospital with acute hip fracture. The HFS pilot project used existing hospital personnel and facilities and initiated new practices, including set protocols, preprinted orders, and standardized assessments, to achieve and evaluate patient triage and care and hospital cost savings. Outcome measures for 91 patients with acute hip fracture consecutively admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 32 publications
(48 reference statements)
4
40
0
Order By: Relevance
“…They found that on average, the co-management hip fracture group saved $13,737 per patient with trends towards improvement in 1-year mortality. Miura et al examined the cost of implementing a geriatrician led hip fracture service in the USA and reported that it was not only cost saving but cost effective [80]. Ginsberg et al performed a cost utility analysis comparing their Sheba model of orthogeriatric management to a reactive orthogeriatric service and concluded that joint care was more cost effective providing additional quality-adjusted life years at a reduced institutional cost per patient [88].…”
Section: Effect Of Orthogeriatric Management On Long-term Functional mentioning
confidence: 98%
See 1 more Smart Citation
“…They found that on average, the co-management hip fracture group saved $13,737 per patient with trends towards improvement in 1-year mortality. Miura et al examined the cost of implementing a geriatrician led hip fracture service in the USA and reported that it was not only cost saving but cost effective [80]. Ginsberg et al performed a cost utility analysis comparing their Sheba model of orthogeriatric management to a reactive orthogeriatric service and concluded that joint care was more cost effective providing additional quality-adjusted life years at a reduced institutional cost per patient [88].…”
Section: Effect Of Orthogeriatric Management On Long-term Functional mentioning
confidence: 98%
“…Recognising those who will benefit from slow-stream rehabilitation and those who have reached a plateau requires experience working with older people and a multidisciplinary approach. Length of stay for patients following hip fracture is often reported as an outcome measure of interest [19] because reductions in length of stay may reflect proactive care and improved clinical outcomes [80]. However, length of stay should be matched to discharge destination and pre-existing levels of independence to ensure that reduction in length of hospital stay does in fact relate to improved clinical outcomes.…”
Section: Effect Of Orthogeriatric Management On Length Of Stay In Hosmentioning
confidence: 99%
“…Some of the published papers describe co-management as the primary intervention with mixed results [8][9][10][11]. The enormity of this problem and high incidence of complications have led to the development of a comprehensive program that combines comanagement of the patient by orthopedic surgeons and geriatricians with lean business principles to create an improved model of patient care [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…This model of care has previously been shown to decrease length of stay (LOS), re-admission rates, complications, costs of care, and in-hospital mortality. 25,[31][32][33][34][35][36] …”
mentioning
confidence: 99%